Correlations of Serum Lipid Parameters and Atherogenic Indices With Left Ventricular Diastolic Dysfunction Among Apparently Healthy Patients With Type 2 Diabetes Mellitus: A Multicenter In-Hospital Cross-Sectional Study - Yves Mayambu Dienda; Jean-Bosco Kasiam Lasi On'kin; Aliocha Nkodila Natuhoyila; Yves Lubenga; Tresor Mvunzi Swambulu; Jean-René M’buyamba-Kabangu; Benjamin Longo-Mbenza; Bernard Kianu Phanzu (Journal of Diabetes Research)
Conclusions: These results highlight the importance of considering atherogenic indices, primarily AIP and CRI-II in the management of T2DM patients. High AIP and high CRI-II could serve as surrogate markers of LVDD, an early cardiovascular manifestation in patients with T2DM.